2011
DOI: 10.2514/1.j050680
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Vortex Generator Model in Adverse Pressure Gradient Boundary Layers

Abstract: The use of a two-dimensional statistical passive vortex generator model, applied to an adverse pressure gradient boundary-layer flow, is evaluated qualitatively against experimental and fully resolved vortex generator computations. The modeling approach taken here has the advantage of substantially reducing the complexity of including such flow separation control devices in a computational mesh, thus giving the opportunity to carry out faster parametric studies. Additional stresses, originating from the vortex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Following Stillfried at al. [59], the vortex velocity field, ( , ), is defined as the difference between the time averaged velocity field, , ( , ) = ( , , ) ̅̅̅̅̅̅̅̅̅̅̅̅ , and the mean flow, ( ) =< , ( , ) >. The latter is obtained by spanwise averaging 〈 〉 over the width of the VG pair.…”
Section: Stereo Pivmentioning
confidence: 99%
“…Following Stillfried at al. [59], the vortex velocity field, ( , ), is defined as the difference between the time averaged velocity field, , ( , ) = ( , , ) ̅̅̅̅̅̅̅̅̅̅̅̅ , and the mean flow, ( ) =< , ( , ) >. The latter is obtained by spanwise averaging 〈 〉 over the width of the VG pair.…”
Section: Stereo Pivmentioning
confidence: 99%
“…Significant reduction of reversed flow in separated region of the bump was observed when counter-rotating vortices were generated. Stillfried et al carried out computations of flow on a bump with various rectangular vortex generator arrays in adverse pressure gradient boundary layer flow [15]. They found that vortex generators should be placed some distance upstream of the separation bubble location.…”
Section: Introductionmentioning
confidence: 99%
“…Reduced efficiency of the SWJ actuators with smaller spreading angle is also consistent with the results about the skew angle of conventional VGJ actuators in the literature. Although there are mixed results about the optimum skew angle of VGJ actuators, an angle between 60° and 90° is reported to be well-suited for separation control studies on an APG ramp [8,25] and variation from 60° to 90° in the skew angle does not cause significant changes in the overall flow features [26]. Although we could not test the SWJ actuators with 180° spreading angle (or 90° skew angle), for the cases tested, and considering the results provided in the literature about the VGJ-skew angle, a spreading angle between 120° and 180° may provide better pressure recovery and thereby may result in better actuator efficiency.…”
Section: The Effect Of Actuator Placementmentioning
confidence: 99%